1995
DOI: 10.1183/09031936.95.08122174
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacterium parvum versus tetracycline as pleural sclerosing agents in rabbits

Abstract: Tetracycline has been one of the most commonly used agents for producing a pleurodesis. However, it is no longer available due to more stringent requirements on the manufacturing process. The objective of this project was to determine whether Corynebacterium parvum is an effective sclerosant in an experimental model in rabbits. The following medications were instilled intrapleurally in anaesthetized male rabbits: tetracycline 35 mg.kg-1 or C. parvum 4 or 8 mg, all diluted with bacteriostatic saline solution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
6
0
2
Order By: Relevance
“…They detected limited inflammation in only one rabbit [18]. Another study of Vargas et al, conducted to compare the effects of pleurodesis initiated by Corynebacterium parvum and tetracycline in rabbits, showed that 4 and 8 mg of Corynebacterium parvum did not cause any fibrogenic effects [19]. In our study, we achieved a powerful and successful outcome with the use of H 2 O 2 , similar to that achieved through talc pleurodesis.…”
Section: Discussionsupporting
confidence: 73%
“…They detected limited inflammation in only one rabbit [18]. Another study of Vargas et al, conducted to compare the effects of pleurodesis initiated by Corynebacterium parvum and tetracycline in rabbits, showed that 4 and 8 mg of Corynebacterium parvum did not cause any fibrogenic effects [19]. In our study, we achieved a powerful and successful outcome with the use of H 2 O 2 , similar to that achieved through talc pleurodesis.…”
Section: Discussionsupporting
confidence: 73%
“…Bleomycin appears to be effective in producing a pleurodesis in patients with malignant pleural effusion [11,19] but not in normal rabbits [20,21]. The intrapleural injection of dried Corynebacterium parvum is effective in controlling malignant pleural effusions [23] but does not produce a pleurodesis in rabbits [22]. It is possible that the presence of the malignancy alters the pleural responsiveness so that a pleurodesis results only when tumor cells are present with these two agents.…”
Section: Discussionmentioning
confidence: 99%
“…A trend for a higher complete response rate in the tetracycline arm might be related to the higher doses used (1.5 g), as suggested by its mechanism of action. In an experimental model, intrapleural tetracycline acts in a dose-dependent way, stimulating mesothelial cells to release a growth-factor-like activity for fibroblasts that induces pleural fibrosis [16,17]. By contrast, the injection of bleomycin was ineffective in creating pleural fibrosis in rabbits with normal pleura, thus suggesting a possible antineoplastic effect [18].…”
Section: Discussionmentioning
confidence: 99%